PH‐Tuned Modulation of 1D Chain to 3D Metal–Organic Framework: Synthesis, Structure and Their Useful Application in the Heterogeneous Claisen–Schmidt Reaction. Issue 3 (8th January 2015) - Sen, Rupam; Saha, Debraj; Koner, Subratanath; Mal, Dasarath; Brandão, Paula; Lin, Zhi
Abstract The role of pH in the formation of metal–organic frameworks (MOFs) has been studied on magnesium‐based carboxylate framework systems [Mg(Pdc)(H2O)3]n (1) and [Mg(Pdc)(H2O)]n (2) (Pdc=pyridine‐2, 3‐dicarboxylate). The investigation reveals the formation of two different compounds of one‐ or three‐dimensions starting from the same reaction mixture that differs only in pH. Isolated compounds have been characterized by IR and elemental analysis; both compounds were also successfully characterized by single‐crystal X‐ray diffraction. This study shows that the gradual increase in pH helps to construct a higher‐dimensional network. Catalytic activity of compounds 1 and 2 was tested for the Claisen–Schmidt reaction. Compound 2 was successfully dehydrated to produce a coordinately unsaturated compound 2 a, which shows higher catalytic activity than 1 or 2 in heterogeneous medium.